Argumen A Fortiori dan Argumen A Contrario dalam Hukum Islam dan Hukum Positif - Marwadi, Marwadi (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
Understanding a law is not only to know explicitly but also to know implicitly. It can be used for finding out the ‘law cause’ or illat as the cause for analogizing the situation. In Islamic law the study of enlarging understanding is wider than positive law since there is a difference between analogical interpretation and a fortiori argument.